2018
DOI: 10.1155/2018/2189348
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Chavicol and Its Synthetic Analogue as Possible Antioxidant and Antilipase Agents Based on the In Vitro and In Silico Assays

Abstract: This study investigated the in vitro and in silico biological properties of the methyl chavicol (MC) and its analogue 2-[(4-methoxyphenyl)methyl]oxirane (MPMO), emphasizing the antioxidant and antilipase effects. MPMO was synthesized from MC that reacted with meta-chloroperbenzoic acid and, after separation and purification, was identified by 1H and 13C NMR and GC-MS. The antioxidant activity was investigated by DPPH, cooxidation β-carotene/linoleic acid, and thiobarbituric acid assays. With the use of colorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Having above mentioned, as well as some data concerning Artemisia plant application in herbal medicine (Nurzyńska‐Wierdak & Grażyna, 2014; Santos et al., 2018), our group decided to check the influence of A. dracunculus EO on microglia cell lines in order to reveal some mechanisms of its antioxidant and protective action.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having above mentioned, as well as some data concerning Artemisia plant application in herbal medicine (Nurzyńska‐Wierdak & Grażyna, 2014; Santos et al., 2018), our group decided to check the influence of A. dracunculus EO on microglia cell lines in order to reveal some mechanisms of its antioxidant and protective action.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the troubles concerning the toxic influence of Artemisia EO two main constituents, estragole and methyleugenol, there is no acute toxicity or mutagenic activity has been reported at doses relevant for human consumption (Pushpangadan & George, 2012). They possess antioxidant and anti‐inflammatory activities (Santos et al., 2018). It was purposeful for us to study the possible antioxidant effect of A. dracunculus EO on some cell models.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EOs and their constituents have been investigated as an alternative additive in the food industry [ 44 , 59 ] in contrast to synthetic antioxidants, such as butylated hydroxytoluene, butylated hydroxyanisole, and propyl gallate, that have exhibited undesired effects to human health [ 60 , 61 ]. Natural compounds from plant EOs which have shown biological activities with potential pharmaceutical applications include ( E )-cinnamaldehyde (antifungal activity, Figure 1 panel A) [ 62 ]; menthol and L-menthol (analgesic activity, panels B and C) [ 63 ]; cuminaldehyde (anticancer activity, panel D) [ 64 ]; eucalyptol and eugenol (anti-inflammatory activity, panels E and F) [ 65 , 66 , 67 ]; and thymol, carvacrol, and methyl chavicol (antioxidant activities, panels G, H, and I) [ 68 , 69 ]. It is important to note that some well-known compounds found in EOs have been recently described with new biological activities, e.g., monoterpenes such as thymol, carvacrol, and p -cymene have been reported to reduce lung emphysema and inflammation [ 70 ] and eugenol has shown activity against several parasites with clinical relevance [ 71 , 72 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…Methyl chavicol, the major compound identified in this oil, has been described by its antimicrobial and antioxidant activities [ 28 ]. Recently, a study identified that this compound and its analogs inhibit the human pancreatic lipase, thus showing a potential application in the treatment of lipid disorders [ 68 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…Thus, spectrophotometric variation of the solution's color (a decrease in absorbance at approximately 470 nm) is representative of the generation of lipid peroxides. The procedure, advantages, and disadvantages of this system have been extensively discussed in the literature [130][131][132][133][134][135][136][137][138], and some examples of the latest LPIP research employing this method are suggested [139][140][141][142][143][144][145][146][147][148][149].…”
Section: Watermentioning
confidence: 99%